Back-Matter JMT Vol 14 No 3 2015 - Manajemen Teknologi, Jurnal (SBM ITB, 2015)
BackmatterÂ Vol 14 No 3 2015 yang berisi: Submission policies,Publication Ethics, Statement Letter, Copyright Transfer Agreement.